1990
DOI: 10.1128/mcb.10.11.5927-5936.1990
|View full text |Cite
|
Sign up to set email alerts
|

The Saccharomyces cerevisiae SIN3 Gene, a Negative Regulator of HO, Contains Four Paired Amphipathic Helix Motifs

Abstract: The SIN3 gene (also known as SDI1) is a negative regulator of the yeast HO gene. Mutations in SIN3 suppress the requirement for the SWI5 activator for expression of the yeast HO gene and change the normal asymmetric pattern of HO expression in mother and daughter cells. Furthermore, the in vitro DNA-binding activity of several DNA-binding proteins is reduced in extracts prepared from sin3 mutants. We have cloned the SIN3 gene and determined that a haploid strain with a SIN3 gene disruption is viable. We determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…late with the methionine phenotype of cells or with derepresincluding some carrying mutations in the SPT21, SIN3, or sion of transcription from the MET25 promoter (Table 1). We SWI2 genes (37,41,50,51). Table 2 shows the relative signals have previously shown the existence of genetic interactions obtained by a quantitative RNase protection assay using RNA between CPF1 and SPT21 and between CPF1 and SIN3 (33).…”
Section: Resultsmentioning
confidence: 95%
“…late with the methionine phenotype of cells or with derepresincluding some carrying mutations in the SPT21, SIN3, or sion of transcription from the MET25 promoter (Table 1). We SWI2 genes (37,41,50,51). Table 2 shows the relative signals have previously shown the existence of genetic interactions obtained by a quantitative RNase protection assay using RNA between CPF1 and SPT21 and between CPF1 and SIN3 (33).…”
Section: Resultsmentioning
confidence: 95%
“…[128][129][130][131][132] Important functional units of the members of the Sin3 family are paired amphipathic a-helix (PAH) domains that contain two amphipathic a-helices separated by a flexible linker and that serve as specific protein-protein interaction domains. 122,133 In fact, PAH1 of Sin3A interacts with the repression domain of the nuclear hormone corepressor N-CoR, 128,134 PAH2 binds to Mad proteins, [122][123][124] and PAH3 is responsible for interaction with SAP30. 132 PML nuclear bodies: glucocorticoid receptor-interacting protein-1 Grip1…”
Section: Perinucleolar Compartment: Paired Amphipathic Helix Protein ...mentioning
confidence: 99%
“…Although the four PAH domains of Sin3 were proposed as sites of protein-protein-interactions (Wang et al 1990), previous studies with a limited number of proteins indicated that PAH1 and PAH2 are mainly responsible for repressor recruitment (Wagner et al 2001;Washburn and Esposito 2001;Sahu et al 2008). We thus systematically investigated which of its domains is contacted by 10 repressor proteins able to bind full-length Sin3 in vitro (not shown: Ume6 for which PAH2 was described as its target site, Washburn and Esposito 2001; Cti6 which binds to PAH1 and PAH2, Aref and Schüller 2020).…”
Section: Sin3-binding Repressor Proteins Interact With Pah1 or Pah2mentioning
confidence: 99%
“…Sin3 was initially characterized in yeast as a negative regulator of mating type switch (repressor of HO: Swi-independent; Sternberg et al 1987; Wang et al 1990) but is strongly conserved in all eukaryotes, being required as an antagonist of cellular proliferation in mammals (Adams et al 2018). In yeast, several unrelated regulatory systems such as phospholipid biosynthesis, phosphate acquisition, sporulation and silencing of hidden mating type loci are affected by Sin3 (Vidal et al 1991), leading to a number of alias gene designations.…”
Section: Introductionmentioning
confidence: 99%